ANALISIS PENGARUH PENDAPATAN PER KAPITA DAN JUMLAH PENDUDUK TERHADAP PERMINTAAN PERUMAHAN DI KOTA LANGSA - Nabila Putri; Safuridar Safuridar; Putty Andini (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of per capita income and population on housing demand in Langsa City. The data used in this study is time series data in the form of per capita income data for Langsa City, the population of Langsa City, and housing demand in Langsa City for the period 2010-2015. Data analysis methods used in this study are multiple linear regression analysis, t test, F test, and analysis of the coefficient of determination. The regression equation in this study is Y = 14.026 + 1.784X1 + 5.035X2. Income per capita has a positive and significant effect on housing demand in Langsa City as evidenced by the t test where tcount > ttable (3.201 > 2.920) and the t sig value is 0.027 <0.05. The population has a positive and significant effect on the demand for housing in Langsa City as evidenced by the t test where tcount > ttable (3.834 > 2.920) and the t sig value is 0.018 <0.05. Per capita income and population simultaneously have a positive and significant effect on housing demand in Langsa City as evidenced by the F test where Fcount > Ftable (15.291 > 9.552) is obtained and the significance level is 0.036 which is less than 0.05. From the analysis of the coefficient of determination (R2) it is known that per capita income and population affect housing demand in Langsa City by 51.2%, while the remaining 48.8% are influenced by other variables not examined in this study